El envejecimiento de la población en Honduras - Hernández Castellón, Raúl; Aguilar, Francisco; Y. Baca, Hector; R. Borjas, Ulda; A. Borjas, Claudio; Borjas, Noemí; Monje, Digna América; Ponce, Victoria; Raudales García, Nelson; Salguero Molina, Sonia (Población y Desarrollo - Argonautas y Caminantes, 2004)
Población y Desarrollo - Argonautas y Caminantes Vol.2 2004 35-57